STRATEGIC LEADERSHIP, INTELLECTUAL CAPITAL, MARKETING ORIENTATION, INNOVATION AND CORPORATE PERFORMANCE: A COMPREHENSIVE MODEL FOR AIRLINES INDUSTRY - Rifandi, Yandri Ahmad; Sazly, Syukron; Islami, Vina; Heirunissa, Heirunissa (Universitas Muhammadiyah Tangerang, 2024)
This study explores the interconnections among strategic leadership, intellectual capital, marketing orientation, innovation, and corporate performance within the airline industry, focusing on PT Garuda Indonesia and PT AirAsia Indonesia. Both airlines demonstrated remarkable recovery from the COVID-19 pandemic, evidenced by significant revenue growth and increased passenger numbers in 2023. Garuda Indonesia's revenue surged to USD 2.93 billion, while AirAsia reported a 75.24% revenue increase to Rp 6.62 trillion. Despite these gains, both airlines faced challenges in aligning aggressive marketing initiatives with operational efficiency, emphasizing the importance of strategic leadership in fostering innovation and managing costs. The research highlights the critical role of human capital in driving innovation and organizational effectiveness. It argues that a strong marketing orientation is essential for meeting customer needs and gaining competitive advantage. To optimize performance, the study recommends that airline executives invest in employee training, adopt a customer-centric approach, and encourage interdepartmental collaboration. Furthermore, leveraging data analytics and monitoring market trends will enable proactive decision-making, ensuring that airlines remain responsive to industry dynamics. In conclusion, this research underscores the intricate connections among strategic leadership, intellectual capital, marketing orientation, innovation, and corporate performance in the airline industry. It highlights that prioritizing human capital development fosters a culture of continuous improvement and creativity, which is essential for adapting to market fluctuations and achieving sustainable growth. A strong marketing orientation allows airlines to align their services with customer demands, enhancing satisfaction and loyalty, which in turn drives corporate performance.